Automated vehicles and sustainability when considering rebound effects - Peter Letmathe; Maren Paegert (PLoS ONE, 2025)
While automated vehicles are expected to lower energy consumption, improve traffic flow and enhance road safety, their deployment may increase traffic volume, leading to a rebound effect. Addressing this issue, we develop a framework to assess the environmental, social and time costs of private and of shared automated vehicle usage in urban and rural areas in Germany. When comparing the status quo and automated vehicle usage, we show that 34–47% of additional traffic volume could emerge without deteriorating current conditions, depending on the area and usage concept. Shared automated vehicles in rural areas constitute the most distinct case, as they are the most beneficial for the environment and society but are the least attractive with respect to the time costs of passengers. Policymakers and system providers should strive to mitigate this dichotomy.